Long-term outcome of prophylactic thyroidectomy in children carrying RET germline mutations. Issue 2 (17th January 2018) - Machens, A; Elwerr, M; Lorenz, K; Weber, F; Dralle, H
Abstract: Background: A comprehensive assessment has not been undertaken of long-term outcomes in children carrying germline RET mutations and undergoing prophylactic thyroidectomy with the aim of preventing medullary thyroid cancer (MTC). Methods: A retrospective outcome study (1994–2017) of prophylactic thyroidectomy in children, with and without central node dissection, was performed at a tertiary surgical centre. Results: Some 167 children underwent prophylactic thyroidectomy, 109 without and 58 with concomitant central node dissection. In the highest-risk mutational category, MTC was found in five of six children (83 per cent) aged 3 years or less. In the high-risk category, MTC was present in six of 20 children (30 per cent) aged 3 years or less, 16 of 36 (44 per cent) aged 4–6 years, and 11 of 16 (69 per cent) aged 7–12 years ( P = 0·081). In the moderate-risk category, MTC was seen in one of nine children (11 per cent) aged 3 years or less, one of 26 (4 per cent) aged 4–6 years, three of 26 (12 per cent) aged 7–12 years, and seven of 16 (44 per cent) aged 13–18 years ( P = 0·006). Postoperative hypoparathyroidism was more frequent in older children (32 per cent in the oldest age group versus 3 per cent in the youngest; P = 0·002), whether or not central node dissection was carried out. Three children developed recurrent laryngeal nerve palsy; all had undergone central node dissection ( P = 0·040). All complications resolved within 6 months. Postoperative normalization of calcitonin serum levels was achieved in 114 (99·1 per cent) of 115 children with raised preoperative values. No residual structural disease or recurrence was observed. Conclusion: Early prophylactic thyroidectomy is a viable surgical concept in experienced hands, sparing older children the postoperative morbidity associated with delayed neck surgery. Abstract : Early surgery better